2002
DOI: 10.1046/j.1365-2133.2002.04694.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking affects collagen synthesis and extracellular matrix turnover in human skin

Abstract: Smoking decreases the synthesis rates of type I and III collagens in skin in vivo and alters the balance of extracellular matrix turnover in skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 33 publications
(38 reference statements)
3
114
0
9
Order By: Relevance
“…Os fibroblastos sofreriam tanto na sua estrutura [15][16][17] quanto na proliferação e diferenciação 13,15,16,[18][19][20] . Nestes estudos estão descritas deficiências da síntese do colágeno 15,17,18,22,23 . Entretanto existem autores que não encontraram mudanças na síntese desta proteína 24,25 .…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
See 1 more Smart Citation
“…Os fibroblastos sofreriam tanto na sua estrutura [15][16][17] quanto na proliferação e diferenciação 13,15,16,[18][19][20] . Nestes estudos estão descritas deficiências da síntese do colágeno 15,17,18,22,23 . Entretanto existem autores que não encontraram mudanças na síntese desta proteína 24,25 .…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Estes efeitos foram também descritos nos osteoblastos, afetando a reconstituição após fraturas 21 . Consequentemente deficiências na síntese do colágeno são relatadas 15,17,18,22,23 . Curiosamente, algumas pesquisas têm mostrado resultados contraditórios.…”
unclassified
“…Le degré d'élasticité de la peau est inversement proportionnel au nombre cumulatif d'heures d'exposition au soleil et de cigarettes fumées. Une étude finlandaise réalisée sur 98 volontaires indique que si les taux de synthèse des collagènes de type I et III sont modérément affectés par le tabagisme, l'activité de la métal-loprotéase 8 est, elle, fortement augmentée chez les fumeurs par rapport aux non-fumeurs dans la classe d'âge de moins de 50 ans [5]. De fait, le tabagisme agit sur de nombreux paramètres impliqués dans le vieillissement de la peau: diminution de synthèse du collagène, augmentation de synthèse des collagénases et de l'élastase, diminution de la micro-circulation, augmentation du stress oxydatif, et modulation de la balance hormonale.…”
Section: Les Effets Du Stress Oxydatif Sur La Peauunclassified
“…Knuutinen et al (2002) noted an increased MMP-8 concentration in the resulting fluid infiltrate in smokers compared to that in the non-smokers following the induction of suction blisters on the upper arm. Furthermore, Betsuyaku et al (1999) have shown increased MMP-8 and MMP-9 activity in the bronchial alveolar lavage fluids of smokers with emphysema compared to those without emphysema.…”
Section: Introductionmentioning
confidence: 99%